421 Specific cephalosporin antibiotics deplete tumor PD-L1 to inhibit DNA damage sensing and sensitize to Chk1 inhibitors in vivo. (April 2022) - Murray, Clare; Kornepati, Anand; Padron, Alvaro; Deng, Yilun; Garcia, Myrna; Bai, Haiyan; Curiel, Tyler
Abstract : OBJECTIVES/GOALS: Tumor PDL1 signals to immune cells for tumor immune evasion but has cell-intrinsic signals that promote tumor virulence. We identify novel tumor PDL1 depleting drugs (PDDs) to interrupt tumor-intrinsic PDL1 signals and sensitize tumors to targeted therapy in vitro and in vivo. METHODS/STUDY POPULATION: We screened the Prestwick and LOPAC libraries for FDA-approved drugs reducing B16 melanoma PDL1 > 2.6-fold. ?-lactam antibiotics were used at 80 ?M and Chk1 inhibitor rabusertib as indicated in T24 human bladder cancer, and murine ID8agg ovarian cancer, 4T1 breast cancer and B16. Genetic PDL1 KO was by CRISPR or shRNA and re-expression by lentivirus. Viability was by MTT and protein by immunoblot. We challenged 5 NSG mice/group with 2x106 T24 (SQ) cells and 5 BALB/c mice/group with 5x105 4T1 cells (mammary fat pad) and treated with cefepime (200 mg/kg), rabusertib (2.5 mg/kg), vehicle, or combo daily from day 3. RESULTS/ANTICIPATED RESULTS: Structurally-related ?-lactam antibiotics cefepime and ceftazidime are tumor PDDs. Cefepime or ceftazidime reduced tumor PD-L1 and thus its cell-intrinsic signals to deplete the DNA damage sensing Chk2 protein and promote rabusertib synthetic lethality in vitro and in vivo in a tumor PDL1-dependent manner independent of immunity. Structurally distinct ?-lactam antibiotics did not sensitize tumor cells to rabusertib, suggesting ?-lactam antimicrobial functions did not promote PDL1 depletion or rabusertib treatment effects in vivo. Although rabusertib effects were immune-independent, both PDDs induced immunogenic tumor STING signaling, suggesting they can improve tumor immunotherapy. DISCUSSION/SIGNIFICANCE: We show a rapidly translatable way to deplete detrimental tumor-intrinsic PDL1 signals, and sensitize tumors to rabusertib. We are testing PDD structure activity relationships to improve PDD effects and testing PDD effects on other treatments, e.g., PARP inhibitors, immunotherapy.